Surface-modified sodium ferric sulfate positive electrode material and preparation method thereof
By using low-temperature plasma deposition technology to build a hydrophobic thin shell on the surface of sodium ferrosulfate positive electrode material, the problem of material sensitivity to air is solved, the hydrophobicity and stability of the material is improved, and the electrochemical performance is improved.
Patent Information
- Application Number
- CN202411485109.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-10-23
AI Technical Summary
The positive electrode material of sodium ferrous sulfate is sensitive to air, resulting in the oxidation of residual alkali and ferrous ions on the surface, increasing the difficulty of pulping and coating, and deteriorating specific capacity and cycling performance.
The water-transporting thin shell layer is constructed on the surface of the sodium ferrosulfate precursor material through low-temperature plasma deposition technology to form a unique core-shell structure to improve the hydrophobic, processing and thermal stability of the material.
It significantly improves the hydrophobicity, processing performance and thermal stability of the material, enhances the stability of the positive electrode structure, prevents the material from being powdered, and improves the transfer efficiency of sodium ions.
Smart Images

Figure CN119627096A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of sodium ion batteries, and in particular relates to a surface-modified sodium iron sulfate positive electrode material and a preparation method thereof. Background Art
[0002] After a long period of development, lithium-ion battery technology has excellent electrochemical properties and is widely used in all aspects of life. However, lithium metal resources are not abundant on Earth. In addition, there is a huge demand for energy storage for renewable energy and grid balancing. Sodium-ion batteries (SIBs) have regained attention as a low-cost alternative to lithium-ion batteries due to their abundant sodium resources and similar chemical properties to lithium. The development of cathode materials using abundant elements on Earth (such as iron) can further reduce costs.
[0003] At present, sodium ion positive electrode materials include layered oxides, Prussian blue and its analogs, and polyanion materials, and different materials have their own advantages and disadvantages. For example, layered oxides are often accompanied by multiple phase changes during the redox and deintercalation of sodium, which leads to structural collapse, thereby affecting the cyclic stability of the material; for example, during the synthesis of Prussian blue materials, the structure is accompanied by a large amount of lattice water, which will decompose and produce a large amount of gas at high potential, causing the battery to swell and fail. Compared with the first two types of materials, sodium iron sulfate, one of the polyanions, has a better application prospect in sodium positive electrodes due to its stable 3D framework structure and excellent electrochemical properties. However, one of the key problems of sodium iron sulfate is its sensitivity to air. Due to the interaction with moisture and oxygen in the air, sodium iron sulfate will have residual alkali on the surface, and some ferrous ions will be oxidized, which increases the difficulty of pulping and coating, and deteriorates the specific capacity and cycle performance.
[0004] The present invention constructs a water-transmitting thin shell layer on the surface of the sodium iron sulfate precursor material through low-temperature plasma deposition technology to form a unique core-shell structure, which greatly improves the hydrophobicity, processing and thermal stability of the material, and can also enhance the stability of the positive electrode structure to prevent the positive electrode material particles from pulverizing during the cycle. At the same time, the core is a carbon-composite conductive active network structure, which is conducive to the transmission of sodium ions. A film with super-hydrophobic properties can be obtained without using any organic surface modifier. The method has the advantages of simple synthesis, green environmental protection, and high film adhesion, and is convenient for industrial production. Summary of the invention
[0005] The purpose of the present invention is to construct a water-transmitting thin shell layer on the surface of a sodium iron sulfate precursor material by low-temperature plasma deposition technology to form a unique core-shell structure, thereby greatly improving the hydrophobicity, processing and thermal stability of the material.
[0006] To achieve the above objectives, the present invention provides the following technical solutions:
[0007] A method for preparing a surface-modified sodium iron sulfate positive electrode material comprises the following steps:
[0008] a. Providing a carbon-composite sodium iron sulfate precursor;
[0009] b. Constructing plasma-deposited hydrophobic group film layer: Fix the mask on the surface of the carbon composite sodium iron sulfate precursor substrate, use a high-frequency plasma generator to prepare a plasma source for the working gas that provides the hydrophobic group, optimize the parameters of low-temperature plasma deposition, and deposit the hydrophobic group on the precursor surface by mask spray deposition, and then remove the mask. Hydrophobic group (-C n H 2n+1 , -CH=CH2 and -C6H5, etc.) are deposited on the surface of the material to obtain a sodium iron sulfate positive electrode material with a core-shell structure.
[0010] In step a, the conductive carbon and zirconium balls are premixed at a low speed, and then an iron source, a sulfur source and a sodium source are added for dry ball milling, and then high-temperature calcination is performed under nitrogen protection, and finally crushing and screening are performed to obtain a carbon-composite sodium iron sulfate precursor. Premixing the conductive carbon tubes and zirconium balls at a low speed in advance can alleviate the agglomeration of subsequent materials to a limited extent.
[0011] In the step a: the precursor chemical formula is Na x Fe y SO4 / C, wherein 0.75≤x≤0.90, 0.55≤y≤0.65 and 1.2≤x / y≤2.
[0012] In the step a, the material of the conductive carbon source can be one or a mixture of one or two of one-dimensional graphite particles, two-dimensional graphene, acetylene black, and three-dimensional single-walled or multi-walled carbon tubes.
[0013] In the step a, the content of the conductive carbon in the total mass of the precursor is 1-5%.
[0014] In the step a, the calcination temperature is 330-380° C., the humidity in the furnace is controlled to be ≤3%, and the calcination is carried out in a nitrogen atmosphere, and the oxygen content in the furnace is less than 5 ppm.
[0015] The crushing and sieving conditions in step a are as follows: air inlet pressure: 0.1-3MPa; air flow crushing frequency: 50-100Hz; classification frequency: 10-150Hz, and the sieving mesh size is 400-500 mesh;
[0016] In the step b: the mesh number of the mask is 50-800 mesh, and the optimal mesh number is 60-100 mesh;
[0017] In the step b, the working gas is gaseous alkanes such as methane, ethane, and propane; gaseous olefins such as ethylene and propylene; gaseous cycloalkanes such as cyclopropane and cyclohexane; gaseous alkynes such as acetylene and propyne.
[0018] In the step b: the deposition temperature of the substrate material is 100-300°C, and optimally 200-250°C.
[0019] The parameters of step b: low temperature plasma deposition are: RF power 100-200W, RF frequency 14MHz, substrate temperature 200-250°C, chamber pressure 50-100Pa, gas flow rate 20-60sccm, and deposition time 10-30min.
[0020] The present invention also provides a surface-modified sodium iron sulfate positive electrode material prepared by the above preparation method.
[0021] The present invention also provides application of the positive electrode material in a sodium ion battery.
[0022] The specific innovative features of the present invention are embodied in the following aspects:
[0023] (1) When the raw materials and the conductive carbon material are bulk-compounded, a good conductive network is formed in the inner core, which is beneficial to the diffusion of sodium ions and thus improves the electrochemical properties of the material;
[0024] (2) The present invention deposits the hydrophobic groups onto the surface of the positive electrode material by spraying the mask, which has better deposition uniformity than direct airflow deposition and avoids the agglomeration of local hydrophobic groups.
[0025] (3) Compared with the CVD process, low-temperature plasma deposition has much lower substrate temperature requirements and is suitable for surface hydrophobic modification of sodium iron sulfate positive electrode materials (which are easily decomposed above 400°C). Compared with other processes using organic hydrophobic surface modifiers, low-temperature plasma deposition avoids the problem of capacity reduction caused by contact between the material and water.
[0026] (4) The present invention constructs a hydrophobic thin shell layer on the surface of the sodium iron sulfate precursor material through low-temperature plasma deposition technology to form a unique core-shell structure. The thin hydrophobic film layer of the shell can be obtained without the use of any organic surface modifier; at the same time, compared with the film layer adsorbed by intermolecular forces, the hydrophobic groups deposited by chemical bonds in this method have higher adhesion and better air stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 Schematic diagram of surface modified sodium iron sulfate positive electrode material.
[0028] Figure 2 for Na0.89 Fe 0.56 SEM image of SO4 / 2%CNTs@film positive electrode material. DETAILED DESCRIPTION
[0029] In order to make the technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0030] Example 1
[0031] The first step is to provide a carbon-composite sodium iron sulfate precursor: weigh 1.75kg of FeSO4, 1.31kg of Na2SO4, and 0.062kg of conductive carbon tubes (CNTs); use dry ball milling to evenly compound, use high-purity nitrogen as a protective gas, press and calcine at 350°C to obtain a sodium iron sulfate precursor. Among them, the proportion of conductive carbon tubes (CNTs) is 2%wt; crush and screen to obtain a sodium iron sulfate precursor with a uniform particle size distribution of 3.0μm;
[0032] The second step is to construct a plasma deposited hydrophobic group film layer:
[0033] (1) Fixing a mask with a certain mesh number on the surface of a sodium iron sulfate precursor substrate with uniform particle size, the mesh number of the mask is: 60 mesh;
[0034] (2) placing the glass substrate in step (1) into a low-temperature plasma deposition chamber, using methane as the working gas, setting the low-temperature plasma deposition parameters, and performing deposition on the substrate.
[0035] (3) The low-temperature plasma deposition parameters are: RF power 250 W, RF frequency 14.0 MHz, substrate temperature 200 °C, chamber pressure 60 Pa, 99.999% pure methane gas flow rate 40 sccm, deposition time 10 min;
[0036] After the film layer is deposited according to the above process, the obtained film layer thickness is 65nm, and the obtained positive electrode material is Na 0.89 Fe 0.56 SO4 / 2%CNTs@film, its structural diagram is as follows Figure 1 As shown in the SEM images Figure 2 shown.
[0037] Example 2
[0038] The first step is to provide a carbon-composite sodium iron sulfate precursor: the process parameters are consistent with those in Example 1;
[0039] The second step is to construct a plasma deposited hydrophobic group film layer: the deposition time is modified to 20 min, and the other parameters are consistent with the process parameters of Example 1;
[0040] After the film layer is deposited according to the above process, the obtained film layer thickness is 75nm, and the obtained positive electrode material is Na 0.89 Fe 0.56 SO4 / 2%CNTs@film.
[0041] Example 3
[0042] The first step is to provide a carbon-composite sodium iron sulfate precursor: the process parameters are consistent with those in Example 1;
[0043] The second step is to construct a plasma deposited hydrophobic group film layer: the gas flow rate of methane working gas is changed to 50 sccm, the deposition time is 10 min, and the other parameters are consistent with the process parameters of Example 1;
[0044] After the film layer is deposited according to the above process, the obtained film layer thickness is 72nm, and the obtained positive electrode material is Na 0.89 Fe 0.56 SO4 / 2%CNTs@film.
[0045] Example 4
[0046] The first step is to provide a carbon-composite sodium iron sulfate precursor: the process parameters are consistent with those in Example 1;
[0047] The second step is to construct a plasma deposited hydrophobic group film layer: the gas flow rate of methane working gas is changed to 60 sccm, the deposition time is 10 min, and the other parameters are consistent with the process parameters of Example 1;
[0048] After the film layer is deposited according to the above process, the obtained film layer thickness is 80nm, and the obtained positive electrode material is Na 0.89 Fe 0.56 SO4 / 2%CNTs@film.
[0049] Example 5
[0050] The first step is to provide a carbon-compounded sodium iron sulfate precursor: weigh 1.75kg of FeSO4, 1.31kg of Na2SO4, and 0.062kg of conductive carbon black (Super P); use dry ball milling to evenly compound, use high-purity nitrogen as a protective gas, press and calcine at 350°C to obtain a sodium iron sulfate precursor. Among them, the proportion of conductive carbon black is 2%wt; crush and sieve to obtain a sodium iron sulfate precursor with a uniform particle size distribution of 3.0μm;
[0051] The second step is to construct a plasma deposited hydrophobic group film layer: the parameters are consistent with the process parameters of Example 1;
[0052] After the film layer is deposited according to the above process, the obtained film layer thickness is 65nm, and the obtained positive electrode material is Na 0.89 Fe 0.56 SO4 / 2%SuperP@film.
[0053] Comparative Example 1
[0054] Preparation of carbon composite sodium iron sulfate precursor: weigh 1.75kg of FeSO4, 1.31kg of Na2SO4, and 0.062kg of conductive carbon tubes (CNTs); use dry ball milling to evenly compound, use high-purity nitrogen as a protective gas, press and calcine at 350°C to obtain a sodium iron sulfate precursor. Among them, the proportion of conductive carbon tubes (CNTs) is 2%wt; the particle size is crushed and sieved to obtain a sodium iron sulfate precursor with a uniform particle size distribution of 3.0μm; the positive electrode material prepared by the above process is Na 0.89 Fe 0.56 SO4 / 2%CNTs.
[0055] Comparative Example 2
[0056] The first step is to provide a carbon-composite sodium iron sulfate precursor: the process parameters are consistent with those in Example 1;
[0057] The second step is to construct a plasma deposited hydrophobic group film layer: the working gas is changed to ethylene with a purity of 99.999%, and the other parameters are consistent with the process parameters of Example 1;
[0058] After the film layer is deposited according to the above process, the obtained film layer thickness is 64nm, and the obtained positive electrode material is Na 0.89 Fe 0.56 SO4 / 2%CNTs@film.
[0059] Comparative Example 3
[0060] The first step is to provide a carbon-composite sodium iron sulfate precursor: the process parameters are consistent with those in Example 1;
[0061] The second step is to construct a plasma deposited hydrophobic group film layer: the deposition time is modified to 5 min, and the other parameters are consistent with the process parameters of Example 1;
[0062] After the film layer is deposited according to the above process, the obtained film layer thickness is 32nm, and the obtained positive electrode material is Na 0.89 Fe 0.56 SO4 / 2%CNTs@film.
[0063] Comparative Example 4
[0064] The first step is to provide a carbon-composite sodium iron sulfate precursor: the process parameters are consistent with those in Example 1;
[0065] The second step is to construct a plasma deposited hydrophobic group film layer: the gas flow rate of methane working gas is changed to 80 sccm, the deposition time is 20 min, and the other parameters are consistent with the process parameters of Example 1;
[0066] After the film layer is deposited according to the above process, the obtained film layer thickness is 150nm, and the obtained positive electrode material is Na 0.89 Fe 0.56 SO4 / 2%CNTs@film.
[0067] Table 1 shows the electrochemical performance results of the surface-modified sodium iron sulfate positive electrode material in a specific embodiment.
[0068]
[0069] As can be seen from Table 1, the surface-modified sodium iron sulfate positive electrode material prepared by the present invention has good processing performance and hydrophobic properties. The optimal CNTs content of the ball-milled composite is 2%. Comparing Example 1 and Example 2, as the plasma deposition time increases, the film thickness increases accordingly, and the rate performance of the material increases, but the gram capacity decreases; Comparing Example 1, Example 3 and Example 4, as the flow rate of the working gas for plasma deposition increases, the film thickness increases accordingly, and the capacity retention rate after 500 cycles increases, but the cyclic reversible capacity decreases; and the rate performance of the material also increases, indicating that a suitable surface hydrophobic film layer can provide a transmission channel for sufficient contact between the core active material and the electrolyte, thereby improving the rate performance of the material; Comparing Example 1, Example 3 and Example 4, as the flow rate of the working gas for plasma deposition increases, the film thickness increases accordingly, and the capacity retention rate after 500 cycles increases, but the cyclic reversible capacity decreases; and the rate performance of the material also increases, indicating that a suitable surface hydrophobic film layer can provide a transmission channel for sufficient contact between the core active material and the electrolyte, thereby improving the rate performance of the material; Example 1 and Example 5 found that when the composite conductive carbon material was changed to acetylene black, the electrochemical performance of the material did not decrease significantly, which was a better material cost reduction direction; Comparative Example 1 and Comparative Example 1 found that when the hydrophobic film layer was not introduced, the electrochemical performance of the material was reduced, and the capacity rate performance of the material without the introduction of the hydrophobic film layer was reduced, indicating that the hydrophobic film layer can effectively reduce the water absorption of the material, thereby increasing the capacity; Comparative Example 1 and Comparative Example 2 found that when the working gas was acetylene, the first cycle coulomb efficiency and reversible capacity of the material were reduced, but the long cycle stability was slightly improved. Comparative Example 1, Comparative Example 3 and Comparative Example 4 found that the thickness of the hydrophobic film layer had a great influence on the physical and chemical properties of the material. When the film thickness was less than 50nm or greater than 150nm, the electrochemical performance of the material was significantly reduced, indicating that the hydrophobic film layer can greatly affect the deintercalation and diffusion of sodium ions in the material system.
[0070] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a surface-modified sodium iron sulfate positive electrode material, characterized in that: The following steps are involved: a. Providing a carbon-composite sodium iron sulfate precursor; b. Constructing a plasma-deposited hydrophobic group film layer: Fix a mask on the surface of a carbon-composite sodium ferric sulfate precursor substrate, use a high-frequency plasma generator to prepare a plasma source for the working gas that provides the hydrophobic group, optimize the PECVD deposition parameters, and deposit the hydrophobic group on the precursor surface by mask spray deposition. Then remove the mask to obtain a surface-modified sodium ferric sulfate cathode material with a core-shell structure.
2. The preparation method according to claim 1, characterized in that: In the step a, the conductive carbon source and the zirconium balls are premixed at a low speed, and then the iron source, the sulfur source and the sodium source are added for dry ball milling, and then high-temperature calcination is performed under nitrogen protection, and finally crushing and screening are performed to obtain a carbon-composite sodium iron sulfate precursor.
3. The preparation method according to claim 2, characterized in that: In step a: the precursor ratio is according to the chemical formula Na x Fe y SO4 / C, wherein 0.75≤x≤0.90, 0.55≤y≤0.65 and 1.2≤x / y≤2, and the carbon content in the total mass of the precursor is 1-5%.
4. The preparation method according to claim 2, characterized in that: In the step a, the conductive carbon source material is one or a mixture of two of one-dimensional graphite particles, two-dimensional graphene, acetylene black, and three-dimensional single-walled or multi-walled carbon tubes.
5. The preparation method according to claim 2, characterized in that: In the step a, the calcination temperature is 330-380° C., the humidity in the furnace is controlled to be ≤3%, and the calcination is carried out in a nitrogen atmosphere, and the oxygen content in the furnace is less than 5 ppm; the crushing and screening conditions are as follows: the air inlet pressure is 0.1-3 MPa; the air flow crushing frequency is 50-100 Hz; the classification frequency is 10-150 Hz, and the screening mesh size is 400-500 mesh.
6. The preparation method according to claim 1, characterized in that: In the step b: the mesh number of the mask is 50-800 meshes.
7. The preparation method according to claim 1, characterized in that: In the step b: the working gas is gaseous alkane, gaseous olefin, gaseous cycloalkane or gaseous alkyne.
8. The preparation method according to claim 1, characterized in that The step b: the deposition parameters of PECVD are: RF power 100-200 W, RF frequency 14 MHz, substrate temperature 200-250° C., chamber pressure 50-100 Pa, gas flow rate 20-60 sccm, and deposition time 10-30 min.
9. A surface-modified sodium iron sulfate positive electrode material prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the surface-modified sodium iron sulfate positive electrode material according to claim 9 in a sodium ion battery.
Citation Information
Patent Citations
Method for preparing inorganic transparent super-hydrophobic film by PECVD (plasma enhanced chemical vapor deposition) technology
CN113373427A
Carbon-coated sodium ferric sulfate positive electrode material, preparation method thereof and battery
CN118507681A
Double-shell modified sodium ferric sulfate positive electrode material and preparation method thereof
CN118811863A
Carbon film deposition method
JP2009041085A
Nuts for extending full threaded bolt
KR1020250055200A